2004
DOI: 10.1143/jpsj.73.2857
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Structures and Spin States of NdBaCo2O5.5

Abstract: Neutron diffraction studies have been carried out on a single crystal of oxygen-deficient perovskite NdBaCo 2 O 5 in the temperature range of 7-370 K. There have been observed, with decreasing temperature T, two magnetic transitions accompanied with structural changes, to the antiferromagnetic phase at ~360 K and to the charge ordered antiferromagnetic one at ~250 K. We have studied the magnetic structures at 300 K and 7 K. At these temperatures the Co-moments have the so-called G -type antiferromagnetic struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…[20][21][22] The Curie point of LaBa-Co 2 O 5.5 is the largest and reaches 326 K. 23 Several studies of the magnetic structure of LnBaCo 2 O 5.5 layered perovskites have been performed with diverging results. [24][25][26][27][28][29][30][31] According to Refs. 27 and 31, the magnetic structure is non-collinear in both antiferromagnetic and ferromagnetic phases.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] The Curie point of LaBa-Co 2 O 5.5 is the largest and reaches 326 K. 23 Several studies of the magnetic structure of LnBaCo 2 O 5.5 layered perovskites have been performed with diverging results. [24][25][26][27][28][29][30][31] According to Refs. 27 and 31, the magnetic structure is non-collinear in both antiferromagnetic and ferromagnetic phases.…”
Section: Introductionmentioning
confidence: 99%
“…5 Soda et al have performed a neutron single-crystal diffraction study of NdBaCo 2 O 5.5 , and it was found that this compound orders antiferromagnetically with a noncollinear G-type structure. 13 Taskin et al proposed a model for the magnetic structure of GdBaCo 2 O 5.5 in which all octahedral Co 3+ ions are in the LS state while the pyramidal Co 3+ ions are in the IS state. 12 The pyramidal Co 3+ ions order ferromagnetically along ͓1,0,0͔, and the coupling between the ferromagnetically ordered planes is antiferromagnetical along the ͓0,1,0͔ direction.…”
Section: Introductionmentioning
confidence: 99%
“…Because the energy differences δE among different spin states are small, a wide variety of physical behaviors related to the spin state change may be realized by controlling the δE value. To investigate how the spin state depends on their material parameters, authors' group has carried out the neutron diffraction measurements on single crystals of the oxygen deficient perovskite RBaCo 2 O 5+δ (R=Nd and Tb), having the linkages of CoO 6 octahedra and/or CoO 5 pyramids, and has also studied transport and magnetic properties on the perovskite Pr 1-x A x CoO 3 (A=Ba, Sr and Ca). [3][4][5][6][7] Results of these studies indicate that δE or Co spin states can be controlled by changing the ionic radii of R 3+ and A 2+ and the average electron number.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate how the spin state depends on their material parameters, authors' group has carried out the neutron diffraction measurements on single crystals of the oxygen deficient perovskite RBaCo 2 O 5+δ (R=Nd and Tb), having the linkages of CoO 6 octahedra and/or CoO 5 pyramids, and has also studied transport and magnetic properties on the perovskite Pr 1-x A x CoO 3 (A=Ba, Sr and Ca). [3][4][5][6][7] Results of these studies indicate that δE or Co spin states can be controlled by changing the ionic radii of R 3+ and A 2+ and the average electron number. Not only detailed differences among local structures around Co ions but also the large difference between the pyramidaland octahedral-arrangements of oxygen atoms affect the δE value or the Co spin state through the change of the crystal field strength and/or the electron transfer energy between the Co ions.…”
Section: Introductionmentioning
confidence: 99%